2018
DOI: 10.1093/cid/ciy1001
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in TLR4 and TNFA and Risk of Mycobacterium tuberculosis Infection and Development of Active Disease in Contacts of Tuberculosis Cases in Brazil: A Prospective Cohort Study

Abstract: Background The role of genetic polymorphisms in latent tuberculosis (TB) infection and progression to active TB is not fully understood. Methods We tested the single-nucleotide polymorphisms (SNPs) rs5743708 (TLR2), rs4986791 (TLR4), rs361525 (TNFA), rs2430561 (IFNG) rs1143627 (IL1B) as risk factors for tuberculin skin test (TST) conversion or development of active TB in contacts of active TB cases. Contacts of microbiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Studies evaluating TLR2 mutations in TB have provided inconsistent results, which limited the interpretation of its role in TB pathogenesis (176,177). Moreover, TLR4 and TLR9 have also been suggested to contribute to TB susceptibility (178)(179)(180).…”
Section: Prr Diversity In Humans and Outcomes Of Mtb Infectionmentioning
confidence: 99%
“…Studies evaluating TLR2 mutations in TB have provided inconsistent results, which limited the interpretation of its role in TB pathogenesis (176,177). Moreover, TLR4 and TLR9 have also been suggested to contribute to TB susceptibility (178)(179)(180).…”
Section: Prr Diversity In Humans and Outcomes Of Mtb Infectionmentioning
confidence: 99%
“…11 Gene polymorphisms that create, alter, or destroy phosphorylation sites have been recognized as functional variants for human diseases, such as prostate cancer (TP53 rs1042522) 12 and tuberculosis (TLR2 rs5743708). 13 Niu et al found that IDUA phosphorylation-related SNPs rs3755955 and rs6831280 exert indirect effects on nearby phosphorylation sites, which could affect the risk of OP. 6 Wang et al recruited 172 OP patients with lowtraumatic fractures and 156 OP patients without fracture to investigate the relationship of two SNPs (rs3755955 and rs6831280) with BMD and fractures.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Gene polymorphisms that create, alter, or destroy phosphorylation sites have been recognized as functional variants for human diseases, such as prostate cancer (TP53 rs1042522) 12 and tuberculosis (TLR2 rs5743708). 13 Niu et al found that IDUA phosphorylation-related SNPs rs3755955 and rs6831280 exert indirect effects on nearby phosphorylation sites, which could affect the risk of OP. 6 …”
Section: Discussionmentioning
confidence: 99%
“…The present study was based on analyses performed retrospectively on a cohort of contacts of pulmonary TB patients, recruited between November 1998 through March 2004. The parent study was reported previously (Cubillos-Angulo et al, 2019). The cases and controls were enrolled in the state of Rio de Janeiro, Brazil where the population is mostly white and brown ('parda, mixed ethnic ancestries) (IBGE, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…In a longitudinal investigation examining TB contacts from Brazil, we recently found that polymorphisms in toll-like receptor 4 (TLR4) and tumor necrosis factor (TNFA) are associated with increased risk of TST conversion and development of active TB (Cubillos-Angulo et al, 2019). Here we investigated in this same cohort whether genetic variation of Type I IFN pathway genes were associated with susceptibility to Mtb infection by examining single nucleotide polymorphisms (SNPs) involved in DNA and RNA sensing: (rs1101998, rs1633256, rs866484 in IFI16-PYHIN1-AIM2 region, rs59633641 and rs10887959 in IFIT5), rs304478 and rs304498 in IFIT1 and the IFN signaling pathway (rs11246213 [IRF7]).…”
Section: Introductionmentioning
confidence: 99%